ChemInform Abstract: Solid‐State NMR Concepts for the Investigation of Supported Transition Metal Catalysts and Nanoparticles. Issue 13 (1st April 2014) - Gutmann, Torsten; Gruenberg, Anna; Rothermel, Niels; Werner, Mayke; Srour, Mohamad; Abdulhussain, Safaa; Tan, Shulin; Xu, Yeping; Breitzke, Hergen; Buntkowsky, Gerd
Abstract Review: 146 refs.